THE CONTRIBUTION OF GROUP GUIDANCE SERVICES ON THE STUDENTS RISKY BEHAVIOR PREVENTION PROGRAM - masnurrima Heriansyah (STKIP Singkawang, 2018)
Nowadays, student’s life was very close to the risky behaviors that can lead to mental health disorders such as smoking, alcohol consumption, drug addiction and premarital sex. Risky behaviors that can interfere students should be prevented so that they could avoid negative things in their life. This study will attempt to show the contribution of group guidance services in providing risky behavior prevention program on the students. This research was used Ex Post Facto Research combined with correlational research and involved the subject of 65 students. The results of the study showed that group guidance services showed contribution in prevent risky behavior to their students by 35% to conclude that group guidance services can used as prevention strategy for risky behavior and give positive sentiment for students about the negative impact of risky behavior. The implication of this research is giving an overview of the importance of guidance and counseling service as the prevention step and as for students to be aware and integrate and avoiding risky behaviors for the sake of their better future.